2019
DOI: 10.1016/j.stemcr.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Neural Networks Highly Predict Very Early Onset of Pluripotent Stem Cell Differentiation

Abstract: Summary Deep learning is a significant step forward for developing autonomous tasks. One of its branches, computer vision, allows image recognition with high accuracy thanks to the use of convolutional neural networks (CNNs). Our goal was to train a CNN with transmitted light microscopy images to distinguish pluripotent stem cells from early differentiating cells. We induced differentiation of mouse embryonic stem cells to epiblast-like cells and took images at several time points from the initial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 26 publications
1
79
0
Order By: Relevance
“…To date, nearly all cell biological 615 applications of this technology have used some form of supervised learning for 616 classification tasks (44). For example, CNNs have been effectively used for cell-by-cell 617 classification with goals including predicting differentiation of stem cells (45), 618 classifying cell cycle status (46), and identifying cell types based on their motility 619 behavior (47). Pixel-by-pixel classification strategies for cell images have also been 620 fruitfully applied to the problem of image segmentation, using human-annotated "ground 621 truth" images for training purposes (48).…”
Section: Recent Advances In the Design Of Deep Convolutional Neural Nmentioning
confidence: 99%
“…To date, nearly all cell biological 615 applications of this technology have used some form of supervised learning for 616 classification tasks (44). For example, CNNs have been effectively used for cell-by-cell 617 classification with goals including predicting differentiation of stem cells (45), 618 classifying cell cycle status (46), and identifying cell types based on their motility 619 behavior (47). Pixel-by-pixel classification strategies for cell images have also been 620 fruitfully applied to the problem of image segmentation, using human-annotated "ground 621 truth" images for training purposes (48).…”
Section: Recent Advances In the Design Of Deep Convolutional Neural Nmentioning
confidence: 99%
“…In particular, the use of these technologies in automation may change the way readings are performed. We have already previously shown that this may be the case using a stem cell differentiation model (10 ). Hence, deep learning algorithms may substitute everyday assays in some circumstances.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, one of the most active field is image recognition (8 , 9 ). We have recently published that NN can be used to classify transmitted light microscopy (TLM) images (10 ). We were able to correctly classify pluripotent stem cell differentiation at one hour or even less, with an accuracy higher than 99%.…”
Section: Introductionmentioning
confidence: 95%
“…In contrast to other established methods such as immunostaining, gene expression analysis, and flow cytometry, cell lines expressing fluorescently tagged proteins offer advantages by enabling non-destructive and minimally invasive assays for tracking the status of cellular function. Deep learning software can be particularly advantageous when analyzing subtle changes in cellular phenotypes from cell imaging data, either by monitoring cultures of iPSCs and early-stage differentiation, 111 determining maturation, or assaying drug responses using experimental cultures. Such methods have recently been validated to determine the quality of iPSC cultures, 112 detect early differentiation changes, 111 and for late-stage analysis such as the categorization of drug responses using iPSC-cardiomyocytes.…”
Section: Cardiomyocytesmentioning
confidence: 99%
“…Deep learning software can be particularly advantageous when analyzing subtle changes in cellular phenotypes from cell imaging data, either by monitoring cultures of iPSCs and early-stage differentiation, 111 determining maturation, or assaying drug responses using experimental cultures. Such methods have recently been validated to determine the quality of iPSC cultures, 112 detect early differentiation changes, 111 and for late-stage analysis such as the categorization of drug responses using iPSC-cardiomyocytes. 113 To generate imaging data with live cells, many engineered reporter iPSC-lines are being developed to aid in the determination of cellular structure and function, including fluorescent reporter lines for structural features 114 and a GCaMP calcium sensor.…”
Section: Cardiomyocytesmentioning
confidence: 99%